2009
DOI: 10.2527/jas.2008-1080
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal piglet husbandry practices and well-being: The effects of alternative techniques delivered separately1,2

Abstract: The aim of this study was to evaluate stress responses evoked by 2 alternative methods for performing the following processing procedures: 1) teeth resection-clipping vs. grinding; 2) tail docking-cold vs. hot clipping; 3) identification-ear notch vs. tag; 4) iron administration-injection vs. oral; 5) castration-cords cut vs. torn. Eight to 10 litters of 8-, 2-, and 3-d-old piglets were assigned to each procedure. Within each litter, 2 piglets were assigned to 1 of 4 possible procedures: the 2 alternative meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
156
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(172 citation statements)
references
References 29 publications
2
156
3
3
Order By: Relevance
“…The different ways to perform the procedure have already been described in order to identify the least stressful method (Sutherland and Tucker, 2011). Marchant-Forde et al (2009) found no effect of treatment on cortisol, but cauterisation produced greater vocalisations and poorer growth rates than cold clipping with side cutting pliers. In Sutherland et al (2008) the blunt trauma cutter group and the cauterisation group equalled at 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…The different ways to perform the procedure have already been described in order to identify the least stressful method (Sutherland and Tucker, 2011). Marchant-Forde et al (2009) found no effect of treatment on cortisol, but cauterisation produced greater vocalisations and poorer growth rates than cold clipping with side cutting pliers. In Sutherland et al (2008) the blunt trauma cutter group and the cauterisation group equalled at 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of tail jamming and tail wagging (Noonan et al, 1994) were greater in tail docked compared with control-handled pigs for up to 90 s after docking. Furthermore, tail docked pigs produced more grunts (Noonan et al, 1994) and higher peak vocal frequencies during tail docking (Marchant-Forde et al, 2009) compared with control-handled pigs. These results suggest that pigs experience pain during and in the hours following tail docking.…”
Section: Introductionmentioning
confidence: 94%
“…It is hard to accurately measure behaviors that are performed infrequently using scan sampling methodologies (Mitlohner et al, 2001). Previous studies have recorded pig behavior and vocalizations during processing in response to different tail docking methods (Noonan et al, 1994;Marchant-Forde et al, 2009). Pain-like behaviors, including tail jamming and tail wagging (Noonan et al, 1994) and vocalizations, including grunts and high-peak vocal frequencies (Marchant-Forde et al, 2009) were greater in tail docked compared with control-handled pigs.…”
Section: Sutherland Davis and Mcglonementioning
confidence: 99%
See 2 more Smart Citations